Transfer matrix method for identifying the dynamic characteristics of an exhaust system / Muhamad Norhisham Abdul Rani - Abdul Rani, Muhamad Norhisham (2008)
There are a number of modelling procedures and methods for the analysis of dynamic characteristics of structures available. The selection of the procedures and methods is very important, in particular the computational accuracy and speed and the operating cost. Numerical technique based on Transfer Matrix Method can be an alternative viable option that offers fast initial prototype solutions for designers. The purpose of the research was to present an alternative method for the identification of the dynamic characteristics of continuous systems or single line type structures in place of commercially available software, in particular at the preliminary design evaluation stage . The natural frequencies and mode shapes of the structures were the items of interest in the dynamic characteristics analysis. The alternative method which is the Transfer Matrix Method was developed based on the wave equations of longitudinal vibration and lateral vibration of beam and numerically supported by FORTRAN source code. For preliminary validation and test of accuracy and efficiency, the developed method was applied to a 3D simple pipe. The numerical results obtained were compared to the results calculated from commercial computer simulation software (MSC PATRANINASTRAN). The results showed good agreement with the maximum contrasting value of natural frequencies was 0.48Hz. The developed method was then applied to a more complex structure which is an exhaust system , considered as a case study of this research. The numerical results of natural frequencies and mode shapes derived from the developed method were again compared to the numerical results obtained from the commercial software. The numerical results of the natural frequencies and mode shapes also showed good qualitative agreement in the comparisons of the results calculated from the commercial computer simulation software. The maximum contradiction of natural frequencies between the developed method and commercial computer simulation (MSC PATRANINASTRAN) was only O.57Hz. The qualitative good agreement between the developed method and commercial computer simulation shows that the developed method offered good capacity and also inexpensive c(')St for identifying the dynamic characteristics of the continuous systems.